Biscoito fortificado com ferro na prevenção e tratamento da anemia em pré-escolares. - Parente, Kelle Maria Tomais (2024)
Iron deficiency anemia is a major public health challenge in Brazil, especially among children.The deficiency affects children's cognition, motor skills, and physical and immunological development, increasing their vulnerability to infections. Food fortification has proven to be very important, promoting the best cost-benefit ratio in terms of treatment. One way to combat or prevent this nutritional deficiency is to add iron to foods that are regularly consumed. In this scenario, the study aimed to evaluate the effects of an iron- fortified biscuit for the prevention and treatment of anemia in preschool children. This is a randomized controlled clinical trial that was conducted at an Early Childhood Education Center in the city of Alcântaras/Ceará. 122 children aged 24 to 36 months participated in the study. The sample was allocated through a cluster randomization, and the classrooms were randomized into two groups: an intervention group (group A), where the children ingested 2 biscuits fortified with 20 mg of elemental iron each, twice a week for 16 weeks, and a control group (group B), in which the children ingested the same biscuits without iron fortification. The biscuits were distributed during school meals by the lunch ladies who were trained by the researcher. Capillary blood was collected from the side of one of the child's fingers, under prior antisepsis, for hemoglobin analysis with the HemoCue portable hemoglobinometer (Hb 301). Collections occurred at the beginning of the study and after the intervention. The data were tabulated and organized in spreadsheets using the SPSS for Windows, version 17.0. The Student's t-test was used to assess the differences between the hemoglobin means before and after the intervention and the Fisher's exact test to assess categorical variables. After the intervention there was a significant increase in hemoglobin in the fortified biscuit group with a mean increase in hemoglobin from 9.88 to 11.49 g/dL, an increase of 1.63 g/dL, with p < 0.0001, associated with a significant decrease in the prevalence of anemia from 80.9% to 11.8%, from 55 anemic children to only 8 children. There was a significant reduction in the prevalence of anemia after the intervention, with the majority of anemic patients achieving normal hemoglobin levels. In our study, the fortification of biscuits with ferrous sulfate proved to be a beneficial intervention, easy to adhere to, well accepted by children and attractive, promoting an increase in Hb levels and reducing the prevalence of anemia.